2014
DOI: 10.1002/pros.22760
|View full text |Cite
|
Sign up to set email alerts
|

In vivo characterization and numerical simulation of prostate properties for non-thermal irreversible electroporation ablation

Abstract: Preliminary experimental IRE trials safely ablated healthy canine and cancerous human prostates, as examined in the short- and medium-term. IRE-relevant prostate properties are now experimentally and numerically defined. Importantly, the electric field required to kill healthy prostate tissue is substantially higher than previously characterized tissues. These findings can be applied to optimize IRE prostate cancer treatment protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
88
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 47 publications
2
88
2
Order By: Relevance
“…Given the incredible redundancy and arborizing nature of Purkinje fibers,23 coupled with the trabeculated nature of the left ventricle, an approach using electroporation may be a promising alternative. Consistent with other noncardiac electroporation patterns of injury, the extent of injury found was not solely reliant on contact and confined to the tissue adjacent to the catheter tip, but a result of the electric field (V/cm) created 24, 25, 26, 27. The ablation electrode was deliberately kept at least 10 mm (and up to 25 mm) away from the Purkinje that was being actively recorded.…”
Section: Discussionsupporting
confidence: 70%
“…Given the incredible redundancy and arborizing nature of Purkinje fibers,23 coupled with the trabeculated nature of the left ventricle, an approach using electroporation may be a promising alternative. Consistent with other noncardiac electroporation patterns of injury, the extent of injury found was not solely reliant on contact and confined to the tissue adjacent to the catheter tip, but a result of the electric field (V/cm) created 24, 25, 26, 27. The ablation electrode was deliberately kept at least 10 mm (and up to 25 mm) away from the Purkinje that was being actively recorded.…”
Section: Discussionsupporting
confidence: 70%
“…Previously, Neal et al described two human IRE cases performed without serious adverse events followed by uncomplicated radical prostatectomies. The histology shows tissue necrosis plus a variable extent of reactive stromal fibrosis, inflammatory infiltrates and regenerative changes in epithelial lining of prostatic ducts 32. So far, several focal therapies have been proposed and investigated for prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The histology shows tissue necrosis plus a variable extent of reactive stromal fibrosis, inflammatory infiltrates and regenerative changes in epithelial lining of prostatic ducts. 32 So far, several focal therapies have been proposed and investigated for prostate cancer. In the past, the first phase I/II assessments of new focal ablation modalities have often been skipped and these methods were immediately used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…IRE has been promoted by different groups as a non-thermal treatment option where ablation only occurs between the inserted electrodes [22,23,24]. The latest publication by van Gemert et al [25] showed a thermal effect in tissues between 67 and 92 °C by IRE.…”
Section: Discussionmentioning
confidence: 99%